1997
DOI: 10.1897/1551-5028(1997)016<2521:teabho>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Trace-Element Accumulation by Hygrohypnum Ochraceum in the Upper Rio Grande Basin, Colorado and New Mexico, Usa

Abstract: Abstract-Accumulation of 12 trace elements by transplanted aquatic bryophytes (Hygrohypnum ochraceum) was determined at 13 sites in the Rio Grande and tributary streams in southern Colorado and northern New Mexico as part of the U.S. Geological Survey's National Water-Quality Assessment Program. The purposes of the study were to determine the spatial distribution of trace elements in relation to land-use practices in the upper Rio Grande Basin, compare accumulation rates of metals in bryophytes at sites contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…1), has been contaminated by molybdenum mine tailings. Elevated concentrations of Cd, Pb, and Cu in sediments and Se, Cd, As, and Zn in fish and other biota in the Red River have been documented (Carter and Porter, 1997;Roy and others, 1992). Some gold and silver mining also occurred historically in Trans-Pecos Texas.…”
Section: Mining and Energy Extractionmentioning
confidence: 93%
See 2 more Smart Citations
“…1), has been contaminated by molybdenum mine tailings. Elevated concentrations of Cd, Pb, and Cu in sediments and Se, Cd, As, and Zn in fish and other biota in the Red River have been documented (Carter and Porter, 1997;Roy and others, 1992). Some gold and silver mining also occurred historically in Trans-Pecos Texas.…”
Section: Mining and Energy Extractionmentioning
confidence: 93%
“…The NASQAN program periodically collected water samples, which were analyzed for a large number of dissolved and suspended constituents including pesticides, nutrients, and trace elements, at six RGB sites sampled in our study (Stations 511-516; Table 1) beginning in 1996 (Wells and Reutter, 1996). In the early 1990s, the NAWQA pro gram studied the upper RGB from its headwaters to El Paso, Texas; the study included the measurement of waterborne pesticides and metals as well as contaminant concentrations in sediments, fish livers (inorganic contaminants), whole fish (organochlorine chemicals) (Carter and Anderholm, 1997;Levings and others, 1998), and bryophytes (Carter and Porter, 1997). White and others (1983) investigated toxaphene and p,p'-DDE concentrations in RGB fish and avian wildlife in the late 1970s; this study included collection sites at Alamosa, Colorado (Station 64), Falcon and Amistad International Res ervoirs (Stations 513 and 514), and the AC at Harlingen, Texas (Station 511).…”
Section: Extant Sources Of Information On Contaminants In the Rgbmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate environmental variability, three bags per site were placed in riffle areas in the stream reach, including the Nate Creek ditch site, for a 15-day exposure period. According to Carter and Porter (1997), the maximum rate of uptake occurs during the first 10-day exposure for most trace elements, and significant differences in bryophyte trace-element concentrations can be found after as few as 10 days of exposure to ambient conditions. Bags were collected and bryophytes were removed and washed again, as described previously, and analyzed for trace elements (Nelson and Camp-bell, 1995;Nelson, 1996).…”
Section: Sample Collectionmentioning
confidence: 99%
“…The use of aquatic bryophytes (mosses) as bioindicators could provide information about the occurrence and bioavailability of trace elements around mining areas. Carter and Porter (1997) found that bryophytes were useful for discriminating stream sites contaminated with arsenic, cadmium, copper, lead, manganese, molybdenum, and zinc, and that they can integrate temporal variations in concentration.…”
Section: Mercurymentioning
confidence: 99%